1994
DOI: 10.1177/039139889401700507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phospholipidic Surface Coatings ex-vivo

Abstract: To evaluate the thromboresistant properties of phospholipidic surface coatings mimicking the lipid surface of blood cells, we studied four different types of phospholipids bound onto PVC tubings in comparison to uncoated as well as heparin bonded controls. The samples analyzed included diacetylenic phospholipid coated as a monomeric treatment (A), diacetylenic phospholipid polymerised prior to being coated (B), and two types of polymeric phospholipids made using methacrylate containing monomers (C and D). A bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…On the basis of this “bioinspired” approach, the phospholipid‐analogous vinyl polymer containing 2‐(methacryloyloxy)ethyl 2‐aminoethyl hydrogen phosphate and a very useful vinyl monomer, 2‐(methacryloyloxy)ethyl phosphorylcholine (MPC), was successfully synthesized 26,27. Since then a vast amount of work has extended the use of MPC, all of which has shown it to suppress protein adsorption,28,29 platelet adhesion,30 thrombus formation,31 and cell adhesion 32. Currently, solutions, hydrogels,33 and nanoparticles34 composed of PC‐polymers are being evaluated as delivery vehicles in cosmetics35,36 and pharmaceutical formulations 37…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this “bioinspired” approach, the phospholipid‐analogous vinyl polymer containing 2‐(methacryloyloxy)ethyl 2‐aminoethyl hydrogen phosphate and a very useful vinyl monomer, 2‐(methacryloyloxy)ethyl phosphorylcholine (MPC), was successfully synthesized 26,27. Since then a vast amount of work has extended the use of MPC, all of which has shown it to suppress protein adsorption,28,29 platelet adhesion,30 thrombus formation,31 and cell adhesion 32. Currently, solutions, hydrogels,33 and nanoparticles34 composed of PC‐polymers are being evaluated as delivery vehicles in cosmetics35,36 and pharmaceutical formulations 37…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to directly reduce the protein and cell adhesion on the surface to minimize the possible adverse effects on blood biochemistry. PPC, by mimicking the membranes of endothelial cells, has a thromboresistance that has been already established .…”
mentioning
confidence: 99%
“…The evidence suggests that PPC may allow a safe reduction of systemic heparinization and there are no cases of heparin‐specific complications using this coating; many studies have demonstrated that PPC can reduce blood loss and thromboembolic complications compared with uncoated circuits . Ranucci et al , in a retrospective study, evaluated PPC circuit versus heparin‐coated circuit and observed that PPC had better preservation of platelet count and lower postoperative bleeding than heparin coating.…”
mentioning
confidence: 99%
“…The coated surface properties are hypothesized to be mainly influenced by the underlying material surfaces 18. In addition to those modifications based on MPC copolymer, some different phospholipids have been bound onto PVC tubing19 to achieve improved blood compatibility. Researchers also applied albumin and heparin multilayer at the surface of medical device to improve the blood compatibility 20.…”
Section: Introductionmentioning
confidence: 99%